Influence of pruning periods on incidence and severity of powdery mildew on ber in northern Karnataka - SHAMARAO JAHAGIRDAR*, M.M. JAMADAR and (Indian Phytopathology, 2004)
The investigations on the effect of pruning periods on powdery mildew incidence were conducted at Regional Research Station, Bijapur during 1998-2001. The studies revealed significantly higher incidence of powdery mildew on early (middle of April) pruned plants on both Umran (32.1%) and Kadaka, CVS (17.2%) as compared to the late (April end to middle of May) pruning conducted. The disease was effectively managed by spraying with recommended schedule (u=15.6% in cv. umran and 5.7% in cv. Kadaka) compared to unsprayed plants (u=56.4% in cv. umran and 31.6% in cv. Kadaka). The incremental increase in the incidence of powdery mildew showed linear pattern right from September to December of each year with its peak being in the month of October in both the cultivars. (Umran = 27.0% and Kadaka = 9.0%).